Potential of sand as a medium of water evaporation – A Review - Humaira, Natasya Ghinna; Hamid, Abdul; Mangkoedihardjo, Sarwoko (Journal of Aridland Agriculture, 2020)
The purpose of this review is to give an up to date overview of the existing literature on water evaporation from the sand. The paper summarizes the factors influencing evaporation rates in water evaporation from sand such as solar radiation, air temperature, air moisture, the temperature at the water-table, relative humidity of the air, depth of the ground water table, wind speed, vapor pressure difference, sand capillary, hydraulic conductivity and particle size of sand. Limitations and constraints identifying existing gaps are discussed, as well as the potential applicability.